THE EFFECT OF THE QUIZLET APPLICATION ON THE VOCABULARY MASTERY OF STUDENTS IN CLASS VII MTS AL-WASHLIYAH BAH GUNUNG - Pratiwy Tanjung, Ayumi (Faculty of Tarbiyah nad Teacher Training, 2022)
This study aims to determine the effect of the quizlet application on the vocabulary mastery observed and researched at Mts Al-washliyah Bah Gunung. This research is conducted using an experimental research design. The population in this study are students of class VII MTs. Alwashliyah Bah Gunung. The sample of the research h is class VII-1 (24 students) as the control class and VII-2 (24 students) as the experimental class. In this study, researchers taught experimentally using the quizlet application and in the control class, researchers taught using conventional methods. Researchers used a pre test, treatment, and post test in this study. In the control class, the score between the pre test and post test increased by 18.12. Meanwhile, in the experimental class the score increased by 21.87. Researcher uses SPSS v.22 to calculate the data. In the post-test control class and experimental class, the researcher finds that the Sig. (2-tailed) on the T-Test is 0.114. > 0.05.